Nitrogen doped amorphous carbon as metal free electrocatalyst for oxygen reduction reaction. (12th January 2017) - Cao, Linmin; Lin, Zhipeng; Huang, Jilin; Yu, Xiang; Wu, Xiaoxian; Zhang, Bodong; Zhan, Yunfeng; Xie, Fangyan; Zhang, Weihong; Chen, Jian; Xie, Weiguang; Mai, Wenjie; et al.
Abstract: A non metal catalyst for the oxygen reduction reaction is prepared by simply pyrolyzing ion exchange resin D113 in NH3 . The product is nitrogen doped amorphous carbon. The pyrolysis of D113 exchanged with iron ion results in nitrogen doped graphitic carbon. The amorphous carbon is easier to be doped by NH3 with higher nitrogen content. The nitrogen doped amorphous carbon is more active than graphitized carbon, together with much improved stability. The higher activity is explained by the higher total nitrogen content and higher pyridinic/graphitic nitrogen percentage. The higher stability is because there is no loss or dissolution of the active sites. The results of this work prove metal element and graphitization of carbon are not necessary factors for nitrogen doped carbon as non noble metal catalyst for the oxygen reduction reaction. Graphical abstract: This work studies nitrogen doped carbon as non metal catalyst for the oxygen reduction reaction. It is found nitrogen doped amorphous carbon shows higher activity than nitrogen doped graphitic carbon. Highlights: Iron element is not necessary for active ORR non noble metal catalyst. Graphitization is not necessary for high ORR activity. Total nitrogen content and pyridinic/graphitic nitrogen percentage influence the ORR activity.